Design Skills, Creativity and Motivation Experimental Study in Russian Art and Design Education - Kadyirov Timur Rashitovich (2025)
The relevance of this experimental study relates from the fact that there is increasing concern on the need for individuals who possess 21st century skills. The constantly evolving society requires people to have professional skills, ideas and the ability to adapt and enhance themselves and their performance. The purpose of experimental study is to discover the influence of Design-Based Learning (DBL) on students’ design skills development, creativity and motivation; their interrelation in the Russian Art and Design Education (ADE). Moreover, to investigate whether the self-created instrument - Toolkit for Studying and Assessing of Design Activity (TSADA) is effective in encouraging creativity and motivation of students during DBL, enabling them to develop and implement design skills and create the product of art-project activity. Study involved 207 Russian ADE field students (M=21.63, SD=3.052). The purposive sampling was used among third-year bachelor students, ranging 19-23 years old. The sample was divided into two groups: control (n=102) where 27 (26.5%) were boys and 75 (73.5%) girls and experimental (n=105) where 29 (27.6%) were boys and 76 (72.4%) girls. Both groups representing diverse ethnicity and varying socioeconomic statuses, but had approximately the same background, level of knowledge and skills. In the experiment, various statistical analysis, such as means (M), standard deviations (SD), inferential statistics (e.g., t-tests, ANCOVA, ANOVA), correlations, regressions, the Rasch analysis, the prediction models, the comparative fit index (CFI), the Tucker-Lewis Index (TLI), the ratios of the correlations of the constructs (HTMT), the standardized root mean square residual (SRMR), and the root mean square error of approximation (RMSEA) were performed. In the pilot study the TSADA was proved effective in Russian ADE, revealing insights on design skills, motivation and creativity (Cronbach’s alpha > 0.90). It showed robust properties in measuring motivation and creativity, with intrinsic (β=0.21, p<.05) and achievement (β=0.54, p<.05) motivation positively impacting creative performance, while extrinsic and failure-avoidance motivation had negative effects on creativity. The main study compared experimental group with DBL under the TSADA treatment and control group with Lecture-Based Instruction (LBI), finding significant improvements of design skills and product of art-project activity in experimental group (M=4.19, SD=0.42). Gender differences were noted, with males showing slightly higher proficiency (M=4.04, SD=0.35), but motivation (β=0.30, p <0.01) and creativity (β=0.22, p <0.05) played more predictive roles in design skill development. The experimental study gives the strong theoretical and practical foundation on design skills, creativity, motivation within ADE and evidence of positive application of self-created TSADA instrument in enhancing art and design competences. It demonstrated how motivation, creativity, students’ design skills and products of art-project activity can be fostered with use of DBL. It provided recommendations for policy makers, researchers, teachers, and other educational stakeholders about constructive and effective methods that should be employed in the class in order to support different learners and encourage them to comprehend educational material. The conducted research expands knowledge in the field of pedagogy, psychology and art and can be useful in enhancing the learning outcomes of students in ADE and overall practice of educators and scholars.